Future Information Technology 6th International Conference, FutureTech 2011, Loutraki, Greece, June 28-30, 2011, Proceedings, Part I - Park, James J.; Yang, Laurence T.; Lee, Changhoon; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This two-volume-set constitutes the refereed proceedings of the 6th International Conference on Future Information Technology, FutureTech 2011, held in Crete, Greece, in June 2011. The 123 revised full papers presented in both volumes were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on future information technology, IT service and cloud computing; social computing, network, and services; forensics for future generation communication environments; intelligent transportation systems and applications; multimedia and semantic technologies; information science and technology.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Computer Communication Networks; Information Systems Applications (incl.Internet).; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Software Engineering; Algorithm Analysis and Problem Complexity